Successful Treatment with Secukinumab in a Psoriasis Patient on Hemodialysis - Xiao Y; Sun J (Psoriasis: Targets and Therapy)
Yu Xiao,1– 3 Jingru Sun1– 3 1Department of Dermatology and Venereology, Peking University First Hospital, Beijing, 100034, People’s Republic of China; 2National Clinical Research Center for Skin and Immune Diseases, Beijing, 100034, People’s Republic of China; 3NMPA Key Laboratory for Quality Control and Evaluation of Cosmetics, Beijing, 100034, People’s Republic of ChinaCorrespondence: Jingru Sun, Department of Dermatology and Venereology, Peking University First Hospital, No. 8 Xishiku Street, Xicheng District, Beijing, 100034, People’s Republic of China, Tel +86-10-83573273, Fax +86-10-66551216, Email sjr12315@126.comAbstract: Moderate to severe psoriasis has been reported as an independent risk factor for IgA nephropathy (IgAN). IgAN is characterized by episodic microscopic hematuria, which can progress to end-stage renal disease (ESRD). Managing therapeutic interventions for psoriasis patients requiring dialysis due to ESRD presents significant challenges. We present a case of severe plaque psoriasis in a patient concurrently diagnosed with IgAN who is dependent on hemodialysis. Over the past two months, his condition has worsened without any identifiable triggers. Physical examination revealed generalized scaly plaques on the scalp, trunk, and extremities, resulting in a Psoriasis Area Severity Index (PASI) score of 19.2. Laboratory tests confirmed end-stage renal insufficiency, with no other abnormalities detected. Consequently, the patient was prescribed subcutaneous secukinumab following a standard regimen. He achieved complete resolution of symptoms after eight weeks of treatment and experienced no recurrence during a one-year follow-up. His kidney-related parameters remained stable during secukinumab therapy. To summarize, this case report discusses a patient with severe psoriasis who also has concurrent IgAN and ESRD, successfully treated with secukinumab. It reinforces the rapid efficacy and enduring safety of secukinumab in managing psoriasis in hemodialysis-dependent patients with IgAN comorbidity. Zeno Fratton et al has reported that an interleukin (IL)-17A/F inhibitor effectively treats moderate-to-severe psoriasis in patients with chronic kidney disease (CKD). However, further studies are necessary to develop evidence-based guidelines for biologic selection within this vulnerable population.Keywords: psoriasis, IgA nephropathy, end-stage renal disease, hemodialysis, secukinumab